Regulation of microRNA expression and function by nuclear receptor signaling - Yang Zhihong (Cell & Bioscience, 2011)
Abstract MicroRNAs (miRNAs) are small non-coding RNA transcripts that affect various cellular pathways by serving as regulators of gene expression at the translational and transcriptional level. Nuclear receptors (NRs) are ligand-activated transcription factors that regulate gene transcription by binding to the promoter region or by interacting with other transcription factors. NRs can regulate miRNA expression either at the transcriptional level, or through posttranscriptional maturation by interacting with miRNA processing factors. This review will summarize recent advances in knowledge of the modulation of miRNA expression by NRs. Increased understanding of the molecular basis of miRNA expression may enable new therapeutic interventions that modulate miRNA activities through NR-mediated signaling.